2017
DOI: 10.1038/s41598-017-03518-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal and fetal LEPR common variants with maternal glycemic traits during pregnancy

Abstract: Recent studies suggested that maternal and placental leptin receptor (LEPR) may be involved in maternal glucose metabolism in pregnancy. To identify maternal and fetal LEPR common variants influencing gestational glycemic traits, we performed association study of 24-28-week maternal fasting glucose, glucose 1 hour after the consumption of a 50-g oral glucose load, fasting insulin and indices of beta-cell function (HOMA-β) and insulin resistance (HOMA-IR) in 1,112 unrelated women and their children. Follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…This might reflect a sort of compensatory regulation between insulin sensitivity/secretion and leptin regulation; indeed, the crosstalk between leptin receptor and insulin resistance has already been documented in other studies 53,54 . As mentioned above, the link between the genetic variants of the LEPR gene, insulin resistance and obesity were confirmed in both children and adults with or without diabetes 55–57 . As expected, our results, coherently with those from former studies, suggest the existence of a leptin receptor resistance that could lead to an alteration of the hormonal feedback, thus causing an increased production of proinflammatory markers at the endothelial level and a concomitant reduction of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…This might reflect a sort of compensatory regulation between insulin sensitivity/secretion and leptin regulation; indeed, the crosstalk between leptin receptor and insulin resistance has already been documented in other studies 53,54 . As mentioned above, the link between the genetic variants of the LEPR gene, insulin resistance and obesity were confirmed in both children and adults with or without diabetes 55–57 . As expected, our results, coherently with those from former studies, suggest the existence of a leptin receptor resistance that could lead to an alteration of the hormonal feedback, thus causing an increased production of proinflammatory markers at the endothelial level and a concomitant reduction of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that LepR can trigger the activation of several pathways, including Pi3K/aKT and Janus-activated kinase/STaT (18)(19)(20). lepr common variant (lepr-common) is reported to influence gestation glycemic traits (21). Leptin is highly expressed in subsets of cancer patients including breast, colon and prostate cancer, and stimulates various biological activities in cancer cells, including cell proliferation, migration and invasion (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%